A comprehensive overview on solar grapes drying: Modeling, energy, environmental and economic analysis. (October 2021) - Srivastava, Ankit; Anand, Abhishek; Shukla, Amritanshu; Kumar, Anil; Buddhi, D.; Sharma, Atul
Highlights: The initial moisture content in all grape varieties found in the range of 70–80% and reduced to 15–20%. Mixed-mode or a hybrid solar dryer reduces the drying time of grapes by 30–40%. PCM integrated dryer needs 10–20% less time to attain grapes' final moisture content. The actual benefits of solar dryers are higher-quality raisin production with lower carbon emissions, a shorter payback period (1–5 years), and a long service life (15–30 years). Abstract: This paper reports different solar dryers primarily designed for grapes drying. Many common solar dryer types, some typical variants, and limitations of traditional grape drying methods are discussed. Functional and economic studies have shown that drying grapes with solar energy is feasible at a lower cost. Due to significant initial investment and low dryer power, solar grape drying commercialization has not, as expected, gained traction. Also, farmers' acceptance of tested solar dryers is not encouraging. Various solar dryers used in grapes drying having a payback period of 1-5 years with an extensive service life of 15–30 years. The indirect solar dryer gives better quality raisins in contrast to the direct type solar dryer because direct exposure to sunlight harms the texture and color of raisins. Mixed-mode type dryers and hybrid type dryers require 15–25% more initial investment than an indirect solar dryer but drying time reduces 30–40% when using mixed-mode and hybrid technology. For the prediction of the drying behavior of grapes, mathematical models such as the Two-term & Midilli model were found best. Simulation software conducts a numerical analysis that predicts air velocity and temperature profiles to dry grapes. It estimates the exact shape and size of the solar dryer and saves money which is expermintally a prolonged exercise. For evaluating the performance of solar dryers, three criteria, i.e., energy analysis, economic analysis, and environmental impacts, are the most important, showing the actual benefits of solar dryers. These solar dryers also promote the reduction of carbon emission and thus helps in earning carbon credit.